Constrains in commercialization of watermelon (Citrullus lanatus) Cultivation in Africa—a review (Current Horticulture, 2024)
Watermelon, [Citrullus lanatus var. lanatus L] is a major crop in Africa, especially facing the harsh effects of climatic change.Itis a xerophytic cropthat can be grown in subtropical andtropicalparts ofthe world. Some constrains in commercialization of watermelon production are related to agronomic practices, post-harvest management and value-addition in Africa. Several products can be made from watermelon seeds, rind as well as their pulp, thereby boosting the food industry through its materials. However, watermelon production in Africa is hindered by several constrains, like weeds, pests, diseases and poor post-harvesting management. For the realization of true potential of watermelon production in Africa, more research is needed to come up with varieties which are tolerant to pests, diseases and weeds. The awareness in communities on its importance as a commercial crop in drought-prone areas also need attention.
Keywords: Curcubit; Post-harvest management; Watermelon seeds; Xerophyte; Climatic change